Microbiota Diversity Associated with Midgut and Salivary Gland of Aedes aegypti and Aedes albopictus (Tribhuvan University Journal of Microbiology, 2023)
Objective: The gut and salivary gland contain diverse micro biota and play an important role in vector competence and disease transmission. In light of this, this study aimed to screen the salivary gland and midgut microbiota associated with Aedes aegypti and Aedes albopictus from Kathmandu and Lalitpur districts of Nepal.Methods: An analytical cross-sectional study was conducted from April 2017 to October 2017 in Kathmandu and Lalitpur districts of Nepal. The fi eld collected mosquitoes larvae were reared in the laboratory until the adult emergence and identified morphologically using standard key. The dissected salivary gland and gut samples were homogenized, suspended in phosphate buffered saline and inoculated in the culture media for bacterial growth which were further identified.Results: Pseudomonas aeruginosa was predominant bacteria in the gut and salivary gland of Ae. aegypti. Similarly, in Ae. albopictus, Serratia marcescens was predominant in gut while, Acinetobacter spp. was predominant in salivary gland. Simpsons diversity index (D), Shannon weaver diversity index (H) and Evenness (E) were found to be the highest viz, 0.81, 1.83 and 0.88 in the gut of Ae. aegypti.Conclusion: This study had provided a comprehensive overview of the bacterial population in the gut and salivary gland of Aedes aegypti and Aedes albopictus. It was found that the most bacterial genera were common to both vectors, although some variation was found in gut and salivary gland. This distribution suggests that there are no host-specific bacterial genera.